Toward Shariah-Compliant Contract Governance in Islamic Banking Spin-Offs: Legal Reflections on Indonesia’s Law No. 4/2023 - Mahfudz, Akhmad Affandi; Firdaus, Iqbal Maulana; Kuanova, Laura Kuanova (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2025)
Indonesia’s Law No. 4/2023 requires Islamic banking units (UUS) to spin off into independent Islamic commercial banks (BUS), raising Shariah compliance concerns over ongoing contracts. This study examines three key contracts—musyārakah, muḍārabah, and ijārah—using qualitative analysis of laws, fatwas, and institutional documents. It identifies four key issues: early termination, defaults during restructuring, unclear asset transfers, and changes in contract objects. These issues threaten both Shariah integrity and legal certainty. The paper proposes a governance framework grounded in qawāʿid fiqhiyyah and maqāṣid al-sharīʿah to guide ethical contract transitions. The findings offer practical insights for regulators, Shariah boards, and industry stakeholders to align legal reforms with Islamic principles. Abstrak:UU No. 4/2023 mengharuskan Unit Usaha Syariah (UUS) bertransformasi menjadi Bank Umum Syariah (BUS), menimbulkan persoalan kepatuhan syariah atas kontrak berjalan. Studi ini mengkaji tiga akad utama—musyarakah, mudharabah, dan ijarah—dengan analisis kualitatif terhadap regulasi, fatwa, dan dokumen kelembagaan. Ditemukan empat isu utama: pemutusan dini, gagal bayar saat restrukturisasi, pengalihan aset yang tidak jelas, dan perubahan objek akad. Masalah ini berisiko melemahkan kepastian hukum dan integritas syariah. Studi ini menawarkan kerangka tata kelola berbasis qawāʿid fiqhiyyah dan maqāṣid al-sharīʿah untuk menjamin transisi kontrak yang etis. Temuan memberikan panduan bagi regulator, DPS, dan industri agar reformasi hukum selaras dengan prinsip syariah.